Kesepian dan Non-suicidal Self-injury pada Emerging Adults yang Orang Tuanya Bercerai - Indri Nopiyanti; Zulfa Febriani (Jurnal Online Psikogenesis, 2025)
Parental divorce often has profound psychological effects on children, one of which is loneliness. In some cases, loneliness has been shown to be one of the factors associated with non-suicidal self-injury (NSSI). NSSI is commonly performed to regulate emotional state (intrapersonal function) or to influence others (interpersonal function), and the prevalence is high among emerging adults. They are in a transitional crisis phase between adolescence and adulthood, facing challenges such as romantic relationships, educational and career choices, and becoming independent from their parents. Therefore, this study aims to investigate the role of loneliness in non-suicidal self-injury among emerging adults with divorced parents. This is a quantitative study using the Inventory of Statements About Self-injury (ISAS) questionnaire to measure NSSI behavior and functioning, and the UCLA Loneliness Scale Version 3 to measure loneliness levels. Participants were selected using purposive sampling, totaling 56 emerging adults (M = 22.2 y.o, SD = 2.4) from divorced families who had engaged in self-injury. Based on the results of simple linear regression analysis, loneliness significantly contributed to NSSI in terms of intrapersonal functioning, accounting for 16.8% (F (1,54) = 10.91, p < .05, R2 = .168). However, loneliness did not significantly influence NSSI in terms of interpersonal functioning (F (1,54) = 1.631, p = .207). Therefore, supportive social resources from family members and peers, as well as counselling programs, may be recommended to prevent NSSI among emerging adults from divorced families.